3D Cu-doped CoS porous nanosheet films as superior counterelectrodes for quantum dot-sensitized solar cells. (September 2015) - Peng, Shengjie; Zhang, Tianran; Li, Linlin; Shen, Chao; Cheng, Fangyi; Srinivasan, Madhavi; Yan, Qingyu; Ramakrishna, Seeram; Chen, Jun
Abstract: Quantum-dot sensitized solar cells (QDSCs), as a promising type of new generation photovoltaic devices, require an efficient and inexpensive counterelectrode (CE) for their commercial application. In this work, novel noble-metal-free Cu-doped CoS (Cu–CoS) CEs are designed for QDSCs. The hierarchical three-dimensional (3D) Cu–CoS porous nanosheet films on fluorine doped tin oxide (FTO) glass are prepared by a simple hydrothermal reaction followed by a cation exchange reaction process. As an alternative to Pt electrode, the 3D structure of porous Cu–CoS nanosheets with high reflectivity can provide a great large number of active catalytic sites and easy accessibility toward S n 2 − / S 2 − electrolyte solution, leading to high electrocatalytic activity. Theoretical calculations are further performed to demonstrate the superior catalytic activity for the Cu–CoS CE. As a result, the QDSC with an optimized Cu–CoS CE exhibits a high photovoltaic conversion efficiency of 6.1% under 100 mW cm −2 irradiation, which is much higher than that of the references Pt and bare CoS CEs. Furthermore, this QDSC device shows long-term stability, which makes it as a very promising and low cost effective material for QDSCs. Graphical abstract: A novel noble-metal-free Cu–CoS counterelectrode, which is prepared by a facile hydrothermal reaction followed by a cation exchange reaction process, is applied in quantum-dot sensitized solar cells, which exhibit superior photovoltaic performance. Highlights: 3D Cu–CoS porous nanosheet films are prepared by a facile chemical method. The noble-metal-free Cu–CoS CEs are designed for QDSCs. The porous Cu–CoS nanosheet film possesses high optical reflectivity. The QDSC with an optimized Cu–CoS CE exhibits a high photovoltaic performance. Theoretical calculations are further performed to show the superior catalytic activity.